Taking the first step with systems theorizing in information systems: A response. Issue 3 (September 2017) - Demetis, Dionysios S.; Lee, Allen S.
Abstract: We address the commentaries of Robey and Mikhaeil, of Mingers, and of Schultze which provided responses to our paper, "Crafting theory to satisfy the requirements of systems science." We find their responses useful for reflecting on the development of the role of systems theorizing within information systems research and provide our reaction in order to clarify several fundamental considerations pertaining to 1) our proposed set of requirements for systems theorizing, 2) the need for explicit systems theorizing, 3) the supposed overall neglect of systems science, 4) the communicability of systems theory and the path of grand theories, 5) emergence, the observer, and other considerations, and 6) systems theory from the perspective of sociomateriality. Highlights: Re-introduces the rightful place of systems theory in IS research. Reflects on the developed set of systems requirements by Demetis & Lee. Responds to commentaries offered by Robey and Mikhaeil, Mingers, and Schultze.